LA DIVINA EUCARISTIA E L’UNITÀ DELLA CHIESA ROMENA CON IL ROMANO PONTEFICE - GEFAELL, Pablo (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2022)
The Divine Eucharist and the Unity of the Romanian Church with the Roman Pontiff. The body of our Lord Jesus Christ, indeed present, real and substantial under the species consecrated in the sacrament of the Holy Eucharist, is inseparable from the mystical body of Christ which is the Church, so that in every valid Eucharistic celebration, the Church of Christ is found. The valid celebration of the Eucharist requires, at least from an objective point of view, communion with the whole Church seen as a visible society. This communion is full if it is carried out both emotionally and effectively around the one who is the social and visible guarantor of unity in the Church; the one who, by the fundamental will of Christ, is the successor of St. Peter, is the Roman Pontiff. Therefore, the path to unity is the path to ecclesial fullness. The Romanian Greek-Catholic Church United with Rome, reached this fullness. REZUMAT: Dumnezeiasca Euharistie și unitatea Bisericii Române cu Pontiful Roman. Trupul Domnului nostru Isus Cristos, prezent într-adevăr, real și substanțial sub speciile consacrate în sacramentul Sfintei Euharistii, este inseparabil de trupul mistic al lui Cristos care este Biserica, astfel încât, în fiecare celebrare euharistică validă se regăsește Biserica lui Hristos. Celebrarea validă a Euharistiei necesită, cel puțin din punct de vedere obiectiv, comuniunea cu întreaga Biserică, văzută ca societate vizibilă. Această comuniune este deplină dacă se realizează afectiv și efectiv în jurul celui care este garantul social și vizibil al unității în Biserică; cel care, prin voința fundamentală a lui Cristos, este succesorul Sfântului Petru, Pontiful Roman. Prin urmare, calea spre unitate este calea spre plinătatea eclezială. Biserica Română Unită cu Roma, Greco-Catolică, a ajuns la această plinătate. Cuvinte-cheie: Eucaristia, comuniune eclezială, unitate, credință, Pontiful Roman.